Andrew Shanks, German Idealism, and the Speculative Redemption of Theodicy. (17th June 2020) - O'Regan, Cyril
Abstract: In this review essay I discuss and critically evaluate the neo‐Hegelian theologian Andrew Shanks' Theodicy Beyond the Death of 'God' with regard to its central argument of the theological adequacy of the composite theodicy funded by Hegel, Jacob Boehme (1575‐1624) and F. W. J. Schelling and also its highly individual theological style. While I commend Shanks' impulses to enlarge the Hegelian discourse by speculative discourses that are more mythopoetic, especially given Shanks' long‐standing interest in the critical and constructive power of poetry, I consider it to be an open question not only as to whether Shanks has sustained his case for the theological adequacy of the composite theodicy, but whether this composite speculative matrix has the capacity to enlist the prophetic discourses of both the Bible and modern poetry that Shanks thinks it has. In addition, while Shanks' theological style is a unique blend of disciplined analysis with a more hortatory rhetoric, as rendered in this his latest book, the generally polemical tone and the tendency to dismissive judgments not only regarding particular philosophers and theologians, but also particular forms of historical Christianity such as Roman Catholicism, compromise – if not entirely invalidate – its repeated message of inclusion.